Five‐year experience with infliximab: Follow up of the product familiarisation program. (16th September 2015) - Nguyen, Rebecca; Braue, Anna; Baker, Chris; Foley, Peter
Abstract: This 5‐year retrospective analysis is of 22 patients who participated in the product familiarisation program (PFP) at St Vincent's Hospital Melbourne, prior to the listing of infliximab on the Pharmaceutical Benefit Scheme. Criteria for inclusion were being an adult with chronic plaque psoriasis, having a psoriasis area and severity index (PASI) score of at least 15 with an inadequate response or intolerance to three of the following: phototherapy, acitretin, cyclosporin and methotrexate. Participants were infused with infliximab 5 mg/kg on the standard induction (weeks 0, 2 and 6) and maintenance (8‐weekly) protocols. At each visit PASI and dermatology life quality index (DLQI) scores were recorded. Success was determined as the proportion of patients achieving at least a 75% improvement in the PASI score from baseline (PASI 75). At 60 months after commencement of therapy, 31% of patients remained on infliximab. Those who did retained PASI 75 with a DLQI of 0 or 1. Of those who ceased infliximab, nine did so due to loss of efficacy, three for personal reasons, two for serious adverse events and one was lost to follow up. Adverse events included non‐melanoma skin cancers, infections and abnormal liver enzymes. Infliximab in the Australian context has proven to be a highly effective treatment of chronic plaque psoriasis, and patients who remained on the drug derived a high level of satisfaction, assessed both subjectively (DLQI) and objectively (PASI 75). The variable response indicates that psoriasis is a heterogeneous disease and investigation into potential patient selection for treatment in the future is warranted.